OTU-02 Per-oral Endoscopic Myotomy (POEM) for oesophageal motility disorders: predictors of treatment success from 103 procedures. Issue 2 (June 2019) - Patel, Mehul; Gulati, Shraddha; Gunasingam, Nishmi; Haji, Amyn; Hayee, Bu'Hussain
Abstract : Introduction: Per-oral endoscopic myotomy (POEM) has gained acceptance as an effective treatment for achalasia and other oesophageal motility disorders but may not be seen as a 'first-line' intervention. Many patients referred for POEM to our institution had, therefore, undergone other therapies and little is known about the influence of this or other factors on treatment outcomes. This study provides an overview of treatment success and safety from our institution. Methods: All patients undergoing POEM since 2013 have been recorded in a registry for baseline characteristics: demographic data, disease classification, previous treatments, manometry, symptoms scores, length of stay (LOS) and procedure parameters. Treatment success was defined as Eckardt score ≤3 and/or reduction by 4 points. Following POEM patients underwent periodic follow-up assessment for: symptoms scores, manometry+pH studies and complications. Results: 103 procedures were performed (98 achalasia, 5 other motility disorders; median disease duration 3.0 y (range 0.3 – 25.0), 46(44.2%) with prior therapy. Median procedure time was 75 min and LOS 2 nights. Success was achieved in 82/91 procedures (90.1%) at 3 months, with significant improvement in median Eckardt scores (8 vs 1, p<0.001) and mean lower oesophageal sphincter pressures (24.9 vs 10.1 mmHg, p<0.001). Success was more likely in those without previous myotomy (93.7% vs 73.4%, p<0.05) with non-significant trends for entirely treatment naïve patients (95.0% vs 82.9%, p=0.077) and duration of disease <2 y (97% vs 83.7%, p=0.058). Adverse event rate was 1.9% (surgical emphysema and periprocedural bradycardic episode). One patient had prolonged hospital admission (12d) due to premature opening of the mucosal entry site. Conclusions: POEM is an effective and safe treatment modality for achalasia and other oesophageal motility disorders. Treatment success is affected by previous myotomy and may be influenced by duration of disease and previous other therapies, making a case for earlier intervention. To better understand predictors of outcome, patient selection factors and long-term outcomes we will be implementing a European registry for POEM to guide referrers and practitioners.